Response of a Rheologically Stratified Lithosphere to Subduction of an Indenter‐Shaped Plate: Insights Into Localized Exhumation at Orogen Syntaxes. Issue 6 (18th June 2019) - Koptev, Alexander; Ehlers, Todd A.; Nettesheim, Matthias; Whipp, David M.
Abstract: This study investigates the influence of the 3‐D geometry of a down‐going plate, the rheological structure of the upper plate, and the migration of the overriding plate toward the trench in relation to the overall subduction velocity on the exhumation pattern in orogen syntaxes. Using a thermomechanical numerical code (DOUAR), we analyze the strain localization, rock uplift, and exhumation response of a rheologically stratified continental lithosphere to subduction of a convex‐upward‐shaped indenter. The models consider three thermorheological lithospheric profiles that determine the degree of mechanical coupling between the upper crust and lithospheric mantle. These models include a strong, cratonic lithosphere; a weaker, younger (and hotter) continental plate; and an intermediate case. The strongly coupled case predicts a localization of high rock uplift rates along narrow linear bands crossing the entire model domain parallel to the trench. In contrast, in a weakly coupled lithosphere, rock uplift is concentrated within a curved ellipse region of anomalously high exhumation rates located above the indenter apex. The aspect ratio of the localized area of rapid rock uplift is controlled by the initial width of the rigid indenter and the relationship between boundary velocities. In particular, the combination of little or no upper plate migration with a narrow indenter causes a nearly circular region ( 100‐km diameter) of rapid exhumation that resembles the pattern of thermochronometer ages observed in orogen syntaxes such as the Southeast Alaska and the Olympic Mountains of the Cascadia subduction zone (western USA). Key Points: Rheological structure of the overriding plate controls resulting deformation pattern Isolated indenter‐centered rock uplift develops in a weakly coupled plate only Narrow indenter excites localized rock exhumation as observed in orogen syntaxes